Family History of Myocardial Infarction Is a Risk Factor for Venous Thromboembolism Among Whites But Not Among Blacks. (July 2013) - Mili, Fatima D.; Hooper, W. Craig; Lally, Cathy; Austin, Harland
In addition to potentially sharing common pathogenesis and clinical manifestations, venous and arterial thromboses might have overlapping risk factors. To evaluate the family history of myocardial infarction (MI) as a risk factor for venous thromboembolism (VTE) among whites and blacks, we analyze data from the Genetic Attributes and Thrombosis Epidemiology (GATE) study. Results indicate that the association between VTE and a family history of MI is statistically significant only among whites (odds ratio [OR] = 1.3; 95% confidence interval [CI] = 1.03-1.8), particularly when they have diabetes mellitus (OR = 3.1; 95% CI = 1.2-8.0). Among blacks, the association between VTE and a family history of MI is not statistically significant (OR = 1.2; 95% CI = 0.89-1.5) either among those with diabetes or those without diabetes. We conclude that a family history of MI is a risk factor for VTE among certain populations stratified by race and comorbid conditions.